MASA KEMUNDURAN PENDIDIKAN ISLAM DAN FAKTOR PENYEBABNYA - Nesa Apriyanti; Sri Ulfa Yunanda; Sinta Dewi; Tantri; Nabila; Sriliza (CV. ADIBA AISHA AMIRA, 2026)
This study examines the decline of Islamic education and its contributing factors from classical to modern times. The research focuses on madrasah quality, teacher roles, socio-economic influences, colonial impact, and the lack of curriculum modernization. The study uses a literature review method based on books and references on Islamic education. Findings indicate that curriculum stagnation, low teacher competence, limited facilities, and socio-economic influences are the main factors in the decline of Islamic education. Lack of adaptation to contemporary needs has caused Islamic education to lag behind modern formal schools. The study emphasizes the importance of curriculum innovation, competent teachers, and creative learning strategies to ensure that Islamic education remains relevant and instills values of worship and ethics in young generations.